2010
DOI: 10.1016/j.ijsu.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the complication rate in Liechtenstein hernia repair

Abstract: The most significant predictive variables of complications in Lichtenstein hernioplasty are the type of closure, antibiotic prophylaxis, ASA risk and the presence of previous recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…9 Just E and Botet X et al in their study titled Reduction of complication rate in Lichtenstein hernia repair done in Department of General Suregry, Hospital Alt Penedes, Barcelona , Spain found that out of overall cases operated, 155 (7.7%) wounds developed complications, 74 of which (3.7%) were haematomas, 44 (2.2%) infections, 27 (1.3%) seromas, and 10 (0.5%) were complications from other causes. 10 Lloyd D Mclean in his editorial "Repair of Inguinal Hernia" said that Excellent results with very low recurrence rates (less than 5%, frequently less than 1%) have been reported for primary repair of inguinal hernias by these techniques by surgeons with large experience and dedicated interest.…”
Section: Discussionmentioning
confidence: 99%
“…9 Just E and Botet X et al in their study titled Reduction of complication rate in Lichtenstein hernia repair done in Department of General Suregry, Hospital Alt Penedes, Barcelona , Spain found that out of overall cases operated, 155 (7.7%) wounds developed complications, 74 of which (3.7%) were haematomas, 44 (2.2%) infections, 27 (1.3%) seromas, and 10 (0.5%) were complications from other causes. 10 Lloyd D Mclean in his editorial "Repair of Inguinal Hernia" said that Excellent results with very low recurrence rates (less than 5%, frequently less than 1%) have been reported for primary repair of inguinal hernias by these techniques by surgeons with large experience and dedicated interest.…”
Section: Discussionmentioning
confidence: 99%
“…LAO uygulanan hastalarda antibiyotik profilaksisi enfeksiyon oranını %1,2'den %0,2'ye düşürmüştür (20). Laparoskopik fıtık onarımında ise bu oran %0,06 olarak bildirilmiştir (21).…”
Section: Grup 1 Grup 2 Grup 3 (N*=30)unclassified
“…6 Konrad Pielacinski, Andrzej B. Szczcepanik, et al in their study done in Warsaw, Poland, discussed that although tension free surgical techniques for inguinal hernia repair have contributed to the improvement of the outcomes as well as the marked reduction of hernia recurrence. These techniques are not free of complications.…”
Section: Monthsmentioning
confidence: 99%